Graphic Design in Vidio Wedding Organization on Dlight Photo Studio - Randi Saputra; Fifi Hasmawati; Sri Hertimi (Universitas Muhammadiyah Palu, 2025)
Dlight Photo Studio has taken an innovative step by integrating graphic design in their wedding videos, not just as a decorative element, but as a medium that conveys the values of love, affection, and wedding aesthetics. Qualitative research is a research method that focuses on understanding the meaning, experience, and views of subjects through in-depth data mining that is descriptive. This research shows that graphic design plays a dual role in wedding videography at Dlight Photo Studio: as an artistic medium that enhances aesthetics and as an effective visual communication strategy to build the studio's image, identity, and competitiveness. It shows that using targeted and innovative graphic design can make audiovisual works not only documentary but also communicative, emotional, and engaging.